Practical autodesk AutoCAD 2023 and AutoCAD LT 2023 : a beginner's guide to drafting and exploring 3D modeling with autodesk AutoCAD /: a beginner's guide to drafting and exploring 3D modeling with autodesk AutoCAD. (2022) - Shoukry, Yasser; Pandey, Jaiprakash
No abstract available